Comparison of Bored Pile Capacity Based on Analytical Design and Pile Load Test – A Case Study - Putri, Karina Meilawati Eka; Fatikasari, Aulia Dewi; Wibisana, Hendrata (Malikussaleh University, Aceh, Indonesia, 2025)
This paper presents a comparative study of bored pile ultimate capacity based on analytical design and field tests. The object of this analysis is the bored pile foundation of the Sei Alalak Bridge in Banjarmasin, Indonesia. The analytical design of pile ultimate capacity was carried out using the empirical methods provided by Reese and O'Neill (1988) and Meyerhof (1976). The calculation of pile ultimate capacity using the empirical method is based on SPT data from four boreholes representing soil data in the abutment, tower, and counterweight zones. Two pile load tests were used to validate the analytical design: pile driving analysis (PDA) and the bi-axial load test Osterberg Cell (O-Cell). The pile ultimate capacity from the empirical method is then compared to field tests regarding pile shaft resistance and end-bearing capacity. The analysis results indicate that the empirical methods tend to underestimate the pile's ultimate capacity by 30–60%. The results reveal that the Reese and O'neill (1988) empirical method generates a significantly lower pile ultimate capacity than Meyerhof (1976). This indicates that the Meyerhof (1976) method gives a closer result of pile ultimate capacity than the field test. On the contrary, the Reese and O'Neill (1988) method is more consistent with the PDA test results. As a result, in this study, the Reese and O'Neill (1988) method is preferred over the Meyerhof (1976) method for predicting the ultimate capacity of a bored pile since it has been demonstrated to be more reliable in estimating the pile's ultimate capacity.